Les liaisons dangereuses : Foucault et la criminologie - Lacombe, Dany (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1993)
With Discipline and Punish, Michel Foucault offered the social sciences a theory of power, and conceptual tools that radically transformed law reform studies. In criminology, for example, the social constructionist tradition, by drawing on Foucault's notion of power, increasingly inscribed law reform studies in a narrative of the dispersal of social control. Attempts to reform the criminal justice system are understood in terms of the increased penetration and expansion of social control into the whole of the social body ; thus, "nothing works !" In this article, I intend to challenge this conventional wisdom on law reform and the dispersion of social control, by demonstrating that it is founded on an essential-ist notion of power that we cannot attribute to Foucault. In light of his work on sexuality, and governmentality, I will examine how Foucault's productive notion of power is better understood in terms of "mechanisms for life", strategies that both constrain — through objectifying techniques — and enable — through subjectifying techniques — agency. The implications of Foucault's productive notion of power for law reform are examined in terms of methodological considerations.